Space - Callery, Sean; Smith, Miranda (New York : Scholastic, 2025)
Explore space in stunning detail with this essential guide to our solar system beautifully packaged with an embossed metal cover. Featuring contributions from renowned space scientists, incredible images, infographics, and the latest information, this book will transport you to planets, stars, and galaxies far beyond.
Starwatch -- Our solar system -- Space travel -- Reaching the stars.
Includes index.
3-6
Keywords: Outer space -- Juvenile literature; Space flight -- Juvenile literature; Solar system -- Juvenile literature; Outer space; Space flight; Solar system